Mechanizmy powstawania oporu podatkowego - Pest, Przemysław (Wydawnictwo Uniwersytetu Wrocławskiego, 2010)
The article presents different theories explaining the formation of tax resistance. At the beginning author shows the possible taxpayers attitudes toward tax like tax compliance, tax avoidance and tax evasion. In the main part of the paper the author describes main psychological and economical theories which explain why taxpayers decide to take a risk and not to comply with their tax liabilities. Moreover, the author presents theories concerning mentality and morality of taxation. In conclusion the author express a need for a research in this area in the future.
Keywords: opór podatkowy; podatnicy; unikanie opodatkowania; uchylanie się od opodatkowania